Analisis Kemampuan Berpikir Kritis Siswa dalam Memecahkan Masalah Soal Cerita Matematika Kelas 1 di SD Negeri Poris Plawad 6 Kota Tangerang - Nur Fitri Damayanti; Siti Nurhayati; Syaeful Bahri (RC-INSTITUT, 2022)
Students' critical thinking skills are indispensable for understanding and solving a math problem or problem that requires reasoning, analysis, evaluation and interpretation of the mind. But if there is no ability and critical thinking ability then students are not able to solve math problems to the maximum. This research aims to describe the level of students' critical thinking skills in solving mathematical problems in the calculation of summation and subtraction operations in grade I of State Elementary School 6 Poris Plawad Kota Tangerang. In this study used 4 indicators of critical thinking skills according to Facione, namely interpretation, analysis, evaluation, and inference. The subjects in the study were grade I students consisting of 32 students. The approach used is a qualitative approach. Data collection techniques are done by conducting written tests and interviews. Data analysis techniques are carried out with the stages of reduction, presentation of data (data display), and conclusion withdrawal (verification). The results of the data analysis showed that: students who are able to think critically are students who are able to meet the overall indicators of critical thinking. Students who are critically capable are being able to meet indicators of interpretation and analysis but are less able to meet evaluation and inference indicators. Students who are low-critical thinking, less able to interpret problems and unable to meet indicators of analysis, evaluation, and inference. He is still less able to understand the problem so that when writing the known and asked is incomplete and when making a mathematical model (mathematical sentence) is not appropriate even does not make it at all because it does not attach importance to the pace of workmanship, and directly answers it with conclusions. In this case, the role of the teacher is very important in training students and getting used to solving training problems so that students' critical thinking skills can develop.